Irrigation System in Khorasan During the Reign of Abu Said Mirza - Muazzamkhon Makhmudova (Scientific Trends, 2025)
This article highlights the high-level attention given by the Timurid ruler Abu Said Mirza to the irrigation system in Khorasan.
Keywords: Abu Sad Mirza, Qutbiddin Tovus Simnoniy, Abdurazzoq Samarqandiy, Juyi Sultoniy canal, Gulistan dam.